Manajemen Kolam Renang di Kabupaten Kebumen Tahun 2020 (Universitas Negeri Semarang, 2021)
The purpose of this study was to find out how to plan swimming pools in Kebumen Regency in 2020, To find out how to organize swimming pools in Kebumen Regency in 2020, To find out how to move swimming pools in Kebumen Regency in 2020, To find out how to supervise swimming pools in Kebumen Regency in 2020. 2020. This research is a qualitative research, the method used to collect data is interviews. The subjects in this study were the owners, managers and visitors of swimming pools in Kebumen Regency. The data analysis technique used is descriptive analysis in a narrative manner. Planning for swimming pool management in Kebumen Regency is done quite well, each swimming pool has a short, medium and long term plan. The organization of swimming pool management in Kebumen Regency is still not going well, some swimming pools do not have a management organizational structure. The implementation of swimming pool management in Kebumen Regency is going quite well, every employee and employee is working satisfactorily. Supervision carried out by swimming pool owners in Kebumen Regency is carried out by verbal coordination, reporting is carried out only based on bookkeeping.